(untitled) (Revista Educação, Artes e Inclusão, 2022)
Considering the importance of art museums and related spaces as loci for the promotion of different aesthetic experiences, we discuss how the configurations and paths of artistic exhibitions can shape the behavior of visitors’ bodies of these spaces. To this end, we have chosen four artistic exhibits for analysis: exhibition “L’ultimo Caravaggio eredi and nuovi maestri” at her Scala Gallery in Milan, Italy (2018); Nathan Sawaya’s “Art of the Brick” exhibition at Oca - Usp in Ibirapuera Park, São Paulo (2016); the exhibition of the fixed collection of Modern and Contemporary Art and, finally, the art workshops promoted by Tate Modern in London, England (2018). These shows express two distinct models. In the Italian and São Paulo exhibitions, the spaces are predetermined and shaped to meet the model conveyed by companies that promote artistic mega exhibitions; in them there is a quick and formatted presence of the visiting bodies. In London exhibitions, there is less rigidity in the setting, providing a greater degree of freedom and slowing the dancing of visitors’ bodies in the exhibition spaces. Therefore, it is noticed that art museums and related spaces are organized from broad educational projects that include a body education of their visitors.